Utilisation of specialist sonographers for head and neck ultrasound fine-needle aspiration cytology can help shorten waiting lists and improve efficiency of the service. Issue 1 (January 2023) - Dave, Roma; Roberts, Simon; Bekker, Jasper; Brennan, Peter A.
Abstract: Head and neck ultrasonography with fine-needle aspiration cytology (FNAC) is recommended by the National Institute for Health and Care Excellence (NICE) and the British Association of Head and Neck Oncologists (BAHNO) for investigating neck masses. Finite specialist radiologists and increased demands on services have increased waiting lists and breached targets. Many patients are on a two-week cancer pathway and accurate investigation cannot be delayed. The implementation of a sonographer trained in neck ultrasound-guided FNAC was analysed together with its impact on the service. Over a 21-month period we have demonstrated a fall in waiting lists from 310 to 28 patients, without compromise to diagnostic accuracy. Additionally, a cost-saving of £60, 000 was made. Improvements in efficiency and waiting lists can be achieved through targeted specialist training for allied health professionals, liberating specialists for other duties.